2019
DOI: 10.1051/matecconf/201930405003
|View full text |Cite
|
Sign up to set email alerts
|

How many RPAS can be safely integrated in non–segregated airspace?

Abstract: The forthcoming integration of Remotely Piloted Aircraft System (RPAS) is one of the cmost omplex challenges for aviation. Europe draws to allow operating RPAS and conventional aircraft in non-segregated airspace by 2025, but this demanding perspective entails a thorough analysis of the different aspects involved. The RPAS integration in non-segregated airspace cannot imply an increase in the safety levels. This paper assesses how the RPAS integration affects safety levels. The goal is to regulate the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…23 Then, the integration of RPAS focuses on reducing their impact on CA; in other words, RPAS must adapt their operations to current ones by reducing their impact on CA. The risk-based framework is composed of three phases depending on the temporary horizon and was developed in previous works 21,24 :• Strategical phase: This phase aims to appraise the impact of RPAS in non-segregated airspace for design purposes. This phase works with basic information of the airspace volume: airway structure and air traffic flow.• Pre-tactical phase: This phase aims to provide airway availability for RPAS in non-segregated airspace for the operational day.…”
Section: Risk-based Methodologymentioning
confidence: 99%
“…23 Then, the integration of RPAS focuses on reducing their impact on CA; in other words, RPAS must adapt their operations to current ones by reducing their impact on CA. The risk-based framework is composed of three phases depending on the temporary horizon and was developed in previous works 21,24 :• Strategical phase: This phase aims to appraise the impact of RPAS in non-segregated airspace for design purposes. This phase works with basic information of the airspace volume: airway structure and air traffic flow.• Pre-tactical phase: This phase aims to provide airway availability for RPAS in non-segregated airspace for the operational day.…”
Section: Risk-based Methodologymentioning
confidence: 99%
“…Additionally, it was suggested that lighter RPAS operate from the airports with lower air traffic density. In the other research on RPAS integration, Pérez-Castán et al (2019a, 2019b, 2019c, 2019d, 2020) were to find the safety metrics, conflict risk assessment and number of RPAS safely operating in the selected Air Traffic Control (ATC) sector in Spain. In this case, the RPAS performances were assumed to be 250 and 450 kt true airspeed (TAS) with standard deviation, respectively, 5 and 20 kt.…”
Section: Introductionmentioning
confidence: 99%